DIMENSI TRANSENDENSI DALAM ANTOLOGI PUISI RAHASIA SANG GURU SUFI KARYA ODHY’S - Gunta Wirawan (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: Transcendence is one of the prophetic ethics initiated by Kuntowijoyo. Observed from the prophetic-sufistic terminology, transcendence can be interpreted as a consciousness of the godliness, it means that what is beyond the limits of humanity. Prophetic ethics is divided into humanization, liberation and transcendence. Although in this study the problem is only focused on the transcendence dimension. The purpose of this study is to describe the meaning of prophetic ethics contained in the anthology poetry Rahasia Sang Guru Sufi work by Odhy's in terms of transcendence dimensions, to deepen the discussion also presented Sufi diction. The method used is hermeneutics qualitative. Based on the results of research, found Odhy's poems contain dimensions that have transcendent weights especially if viewed from a theological and metaphysical perspective. The poet consistently uses the distinctive Sufistic dictionaries such as parks, birds, ponds, roses, alms, oceans, dhikr, tariqat, makrifat, the teacher, mirrors, drunkenness, wine, death and others. The key poem can be called a transcendent poem (tu'minunabillah) of 44 titles of poetry. Odhy's learning tendencies are always related to Sufi issues.Abstrak: Transendensi merupakan satu di antara etika profetik yang digagas oleh Kuntowijoyo. Ditinjau dari terminologi profetik-sufistik, transenden diartikan kesadaran-kesadaran ketuhanan terhadap makna apa saja yang melampaui batas kemanusiaan. Etika profetik terbagi atas humanisasi, liberasi, dan transendensi. Namun, penelitian ini difokuskan pada dimensi transendensi. Tujuan penelitian ini untuk mendeskripsikan makna etika profetik yang terdapat dalam kumpulan puisi Rahasia Sang Guru Sufi karya Odhy’s ditinjau dimensi transendensi. Metode yang digunakan adalah kualitatif dengan strategi hermeneutika. Berdasarkan hasil penelitian, puisi-puisi Odhy’s mengandung dimensi yang mempunyai bobot transendental apalagi jika ditinjau dari perspektif teologis dan metafisis. Penyair konsisten menggunakan diksi-diksi khas sufistik misalnya taman, burung, kolam, bunga mawar, setanggi, laut, samudra, zikir, tarikat, makrifat, sang guru, cermin, mabuk, anggur, kematian, dan lainnya. Puisi-puisi yang dapat diklasifikasikan sebagai puisi transendensi (tu’minunabillah) sebanyak 44 judul puisi yang membuktikan kecenderungan pemikiran Odhy’s selalu terkait dengan persoalan-persoalan sufistik.